Brasil e cobran??a internacional de alimentos - Andrade, Cibelle Cordeiro (2009)
The thesis approaches the charge of allimonies abroad when one of the countries envolved within this process happens to be Brazil. Thefore, along the thesis, one comment the national law as regard do allimonies, both substantially as well as a processuallly. Were studied the two Conventions which Brazil has signed, viz., the Interamerican Convention on Allimonies, as well as the New York Convention, in the same realm. The thesis also studied a recent convention that somewhat complements the ones mentioned. That is, the thesis deals with the The Hague Convention as well. Finally, in order to have a better understanding about the subject there also studied some leading cases which were decided on Brazilian Courts.